Implementasi Nilai-Nilai Karakter Buddhis pada Sekolah Minggu Buddha Mandala Maitreya Pekanbaru - Dharmaji Chowmas (STAB Maitreyawira, 2020)
The purpose of this research was to find out how Buddha Mandala Maitreya Sunday School in Pekanbaru implemented buddhist character values. What Buddhist character values which had been implemented; what method which had been implemented;what obstacles which had been faced by teachers in implementing buddhist characters. This field research was done in Buddha Mandala Maitreya Sunday School in Pekanbaru. Qualitative analysis technique was used as data analysis technique. The result showed the implementation of Buddhism character values in Buddha Mandala Maitreya Sunday School in Pekanbaru. But it was still individually done by each teacher there, there wasn't any specific program or mainly character from Buddha Sunday School or vihara assembly ; the value character which had been implemented were: honesty, mutual respect among friends,obey parents,politeness, sanitation, discipline,and serenity,fond of praying,character and principle practice in daily life, story telling method was used,by providing example in daily life activity, discussion method with student, explained described discpline method,and sharing method. The obstacles which were faced in implementing Buddhism character values were: lack of facility to support, lack of control against students,other problems were students not focus,lack of discipline and still too young, students were still not interested in reading etc.